THE POWER OF HUMAN CAPITAL TO ACHIEVE A COMPETITIVE ADVANTAGE: Survey of the Hospitality Industry in West Java (2022-2023) - Tahir, Rusdin; CK, Taufani; Sandjaya, Teguh (Universitas Padjadjaran, 2024)
The phenomenon of heightened competition in the tourism industry, particularly in West Java, underscores the necessity for star-rated hotels to enhance their competitive advantages. This study aims to investigate the interrelationships among market orientation, human capital, service quality, and competitive advantage within the hospitality sector. Using a quantitative approach, survey research design, and explanatory research objectives, involving hotel guests in West Java. A total of 325 participants were surveyed, yielding 316 valid responses for analysis using Structural Equation Modeling (SEM). The findings indicate that both effective market orientation and quality human capital significantly influence service quality in the hotel industry, both independently and collectively. Moreover, the study demonstrates that market orientation and human capital exert their maximum impact on competitive advantage through improvements in service quality. These insights contribute to theoretical understanding and practical applications in the hospitality sector, emphasizing the need for hotel management to prioritize the development of market orientation and human capital to optimize service quality and, ultimately, competitive advantage. Recommendations include implementing targeted training programs for staff and adopting strategies that align with customer expectations to foster sustained growth and competitiveness in the industry. By addressing these factors, star-rated hotels in West Java can better position themselves in an increasingly competitive landscape.